End-of-the-world branes and inflationary predictions for rocky and swampy landscapes - Friedrich, Bjoern; Hebecker, Arthur; Westphal, Alexander (Journal of high energy physics, 2025)
Making cosmological predictions in a multiverse is a fundamental theoretical challenge. Assuming that (quasi-)de Sitter vacua are quantum mechanically described by a finite-dimensional Hilbert space, we develop a detailed framework for making explicit anthropic predictions. A key challenge which we attempt to overcome arises because, almost unavoidably, cosmologies that asymptote to Minkowski space exist. We then apply our framework to predicting the scale of inflation. We find that, even if eternal inflation is allowed, our predictions depend on creation rates of universes from nothing. These, in turn, are highly sensitive to the existence of end-of-the-world branes. The rates for the creation of universes from nothing are the dominant ingredient for ‘Swampy Landscapes’, which may have no metastable de Sitter vacua but only slow-roll solutions. In ‘Rocky Landscapes’, where long-lived de Sitter vacua are abundant, tunneling rates between such vacua represent a further key factor for deriving predictions.
Gesehen am 10.09.2025